Vivat universitas! 100 years of institutionalisation of sociology at the Belarusian State University - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2021)
The article identifies three stages in the development of sociology at BSU, reveals their content and features. It is argued that the institutionalisation of sociology on the territory of Belarus began with the opening of the Belarusian State University and the creation of the department of sociology and primitive culture, where students were given lectures on genetic sociology, issues of labour, law, cultural history, and sociology of family and marriage. After the identification of historical materialism with sociology, the teaching of sociological disciplines was excluded from the curricula of BSU. Sociology revived in the 1960s with the creation of the Problematic Research Laboratory of Sociological Studies at the BSU. In its depths, as well as in the sector of applied sociology at the department of philosophy of the humanities faculties, personnel were trained and the necessary conditions were created for the opening of the section of sociology and the department of sociology in 1989. Professor G. P. Davidyuk is rightfully considered to be the founder of modern Belarusian sociology. Currently, at BSU, centuries-old traditions in the field of sociological science and education are being developed at the Center for Sociological and Political Researches and at the department of sociology of the faculty of philosophy and social sciences. It is concluded that BSU is one of the leading universities in the post-Soviet space and it possesses everything necessary for its further development. Sociological science and scientific schools are actively developing at BSU. The university staff includes well-known specialists who provide the training of highly qualified personnel with competences to work in conditions of global instability and readiness to give an adequate respond to the new challenges of the time.
Keywords: sociology; Belarusian State University; institutionalisation of sociology; Belarusian sociological school; time-honored tradition; history; stages of development